Long-Lived States of Magnetically Equivalent Spins Populated by Dissolution-DNP and Revealed by Enzymatic Reactions** - Bornet, Aurélien (Chemistry, 2014)
Hyperpolarization by dissolution dynamic nuclear polarization (d-DNP) offers a way of enhancing NMR signals by up to five orders of magnitude in metabolites and other small molecules. Nevertheless, the lifetime of hyperpolarization is inexorably limited, as it decays toward thermal equilibrium with the nuclear spin-lattice relaxation time. This lifetime can be extended by storing the hyperpolarization in the form of long-lived states (LLS) that are immune to most dominant relaxation mechanisms. Levitt and co-workers have shown how LLS can be prepared for a pair of inequivalent spins by d-DNP. Here, we demonstrate that this approach can also be applied to magnetically equivalent pairs of spins such as the two protons of fumarate, which can have very long LLS lifetimes. As in the case of para-hydrogen, these hyperpolarized equivalent LLS (HELLS) are not magnetically active. However, a chemical reaction such as the enzymatic conversion of fumarate into malate can break the magnetic equivalence and reveal intense NMR signals.